Capacity for Seeding and Spreading of Argyrophilic Grain Disease in a Wild-Type Murine Model; Comparisons With Primary Age-Related Tauopathy - Ferrer, Isidro; Andrés-Benito, Pol; Sala-Jarque, Julia; Gil, Vanessa; del Rio, José Antonio (Frontiers in Molecular Neuroscience, 2020)
Argyrophilic grain disease (AGD) is a common 4R-tauopathy, causing or contributing to cognitive impairment in the elderly. AGD is characterized neuropathologically by pre-tangles in neurons, dendritic swellings called grains, threads, thorn-shaped astrocytes, and coiled bodies in oligodendrocytes in the limbic system. AGD has a characteristic pattern progressively involving the entorhinal cortex, amygdala, hippocampus, dentate gyrus, presubiculum, subiculum, hypothalamic nuclei, temporal cortex, and neocortex and brainstem, thus suggesting that argyrophilic grain pathology is a natural model of tau propagation. One series of WT mice was unilaterally inoculated in the hippocampus with sarkosyl-insoluble and sarkosyl-soluble fractions from “pure” AGD at the age of three or seven/twelve months and killed three or seven months later. Abnormal hyper-phosphorylated tau deposits were found in ipsilateral hippocampal neurons, grains (dots) in the hippocampus, and threads, dots and coiled bodies in the fimbria, as well as the ipsilateral and contralateral corpus callosum. The extension of lesions was wider in animals surviving seven months compared with those surviving three months. Astrocytic inclusions were not observed at any time. Tau deposits were mainly composed of 4Rtau, but also 3Rtau. For comparative purposes, another series of WT mice was inoculated with sarkosyl-insoluble fractions from primary age-related tauopathy (PART), a pure neuronal neurofibrillary tangle 3Rtau+43tau tauopathy involving the deep temporal cortex and limbic system. Abnormal hyper-phosphorylated tau deposits were found in neurons in the ipsilateral hippocampus, coiled bodies and threads in the fimbria, and the ipsilateral and contralateral corpus callosum, which extended with time along the anterior-posterior axis and distant regions such as hypothalamic nuclei and nuclei of the septum when comparring mice surviving seven months with mice surviving three months. Astrocytic inclusions were not observed. Tau deposits were mainly composed of 4Rtau and 3Rtau. These results show the capacity for seeding and spreading of AGD tau and PART tau in the brain of WT mouse, and suggest that characteristics of host tau, in addition to those of inoculated tau, are key to identifying commonalities and differences between human tauopathies and corresponding murine models.